Zdravila med dojenjem - Nagelj Kovačič, Nataša (Farmacevtski vestnik, 2008)
Lactation is natural way of feeding and has many benefits for mother and her suckling infant. Many mothers are required to use drugs during breastfeeding. Almost all drugs transfer into breast milk and this may carry a risk for breastfed infant. Factors such as the dose received via breast milk, and the pharmacokinetics and the effect of the drug in the infant need to be taken into consideration. When possible well known and commonly used drugs should beused during lactation.
Keywords: depresija (medicina); dojenje; drug; epilepsija; hipertenzija; infekcije; poporodno obdobje; sladkorna bolezen; zdravila